2022
DOI: 10.1155/2022/8553530
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Susceptibility Loci Identified in GATA2 and ZMIZ1 in Chinese Population

Abstract: Background. Common genetic risk variants for prostate cancer (PCa) have been identified at approximately 170 loci using genome-wide association studies (GWAS), most of which were identified in European populations. Recently, GWAS were applied to a large Japanese cohort and identified 12 novel susceptibility loci associated with PCa risk. In this study, we aim to investigate PCa susceptibility loci in the Chinese population. The study data will be used to promote PCa risk control in China. Methods. A total of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Investigating the mechanisms underlying BCa is crucial for improving the screening and diagnosis of BCa [ 7 ]. Currently, genome-wide association studies (GWASs) have been done in many populations to identify candidate genes associated to the risk of BCa [ 8 ]. A study in Europe demonstrated SNP associations with non–muscle-invasive bladder cancer tumor (size, stage, and grade) and patient characteristics (age and EORTC risk category) at the time of diagnosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigating the mechanisms underlying BCa is crucial for improving the screening and diagnosis of BCa [ 7 ]. Currently, genome-wide association studies (GWASs) have been done in many populations to identify candidate genes associated to the risk of BCa [ 8 ]. A study in Europe demonstrated SNP associations with non–muscle-invasive bladder cancer tumor (size, stage, and grade) and patient characteristics (age and EORTC risk category) at the time of diagnosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study in Europe demonstrated SNP associations with non–muscle-invasive bladder cancer tumor (size, stage, and grade) and patient characteristics (age and EORTC risk category) at the time of diagnosis [ 9 ]. Zhang et al demonstrate that the minor alleles of rs73862213 and rs2335052 in the GATA2 gene and ZMIZ1 gene were remarkably related with the risk of prostate cancer [ 8 ]. Matsuda et al reported that SNPs in the SLC14A1 , APOBEC3A-CBX6 , PSCA , and MYC genes were associated with the risk of bladder cancer in the Japanese population, and a similar association was demonstrated in Chinese, European, and Asian populations [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The haplotype analysis illustrated that the individuals with the A-C-C-A haplotype, constructed with minor allele of rs9900085, and C-C-A-C haplotype, constructed with minor allele of rs8072311, had an increased prostate cancer risk. 22 The results of genotype distributions and haplotype analysis suggested that GAS7 gene is the candidate POAG risk gene. No significant distinction was observed between the cases and controls for rs11656696 and rs74629981, aligning with the Saudi population.…”
Section: Discussionmentioning
confidence: 99%
“…Zmiz1 plays a pivotal role in various biological processes, spanning embryonic development, angiogenesis, immune response, and has been associated with conditions such as cancer, leukemia, and diabetes (11,(39)(40)(41)(42)(43)(44)(45)(46). In recent years, the link between Zmiz1 mutations and NDDs, particularly ASD, has emerged (9, 10, 47-49).…”
Section: Zmiz1 Is An Asd Risk Genementioning
confidence: 99%